Endothelial functional activity and circadian blood pressure dynamics in hypertensive patients treated with angiotensin receptor antagonists - N. G. Poteshkina; G. B. Selivanova; T. Zh. Zhalsaraev (Кардиоваскулярная терапия и профилактика)
Aim. To assess the associations between endothelial functional activity and circadian blood pressure profile (CBPP) in hypertensive patients (Stage I-II arterial hypertension, uncontrolled in ambulatory settings) who were administered candesartan and losartan. Material and methods. The study included 60 patients, aged 35-65 years. All participants were divided into two groups: Group I (n=31; 15 men, 16 women; mean age 46,1±7,1 years) receiving losartan, and Group II (n=29; 12 men, 17 women; mean age 47,2±6,8 years) receiving candesartan. The examination included 24-hour BP monitoring (BPM) and the measurement of serum levels of nitric oxide (NO) stable end products, as the markers of endothelial functional activity. Results. Candesartan demonstrated a more pronounced beneficial effect on several 24-hour BPM parameters, compared to losartan. The candesartan group showed a significant increase in serum NO (NOx) levels (from 38,56±4,68 to 89,17±10,5 μmol/l; p<0,0001). In the losartan group, serum NO (NOx) levels increased from 37,19±2,43 to 59,32±7,03 μmol/l (p<0,001). Serum NO levels significantly correlated with the main CBPP parameters for diastolic BP, both at baseline and during the candesartan treatment. Similarly, the losartan group demonstrated a significant negative correlation between NO levels and 24-hour BPM parameters. Conclusion. The beneficial effects on CBPP and endothelial functional activity were more pronounced for candesartan, compared to losartan.